The convergent total synthesis of cytotoxic homospisulosine and its 3-epi-analogue. Issue 24 (31st December 2015) - Stanková, Kvetoslava; Martinková, Miroslava; Gonda, Jozef; Bago, Martina; Pilátová, Martina; Gönciová, Gabriela
Graphical abstract: Abstract: A common strategy for the total synthesis of cytotoxic homospisulosine7 and its 3- epi -analogue10 was achieved in a stereoconvergent manner, from 3, 5-di- O -benzyl-d -xylofuranose with the efficient use of rearranged products14 –17 . The key transformations of this approach are [3, 3]-heterosigmatropic rearrangements of allylic substrates18 and19 to establish a stereogenic amino group and regioselective intramolecular cyclization to form common oxazolidinones28 and29 . Elongation of the side chain was accomplished via a Wittig reaction. Several compounds were evaluated for their in vitro antiproliferative/cytotoxic activity by the MTT method employing five different human cancer cell lines (Jurkat, MDA-MB-231, MCF-7, HCT-116 and Caco-2). The obtained data revealed that homospisulosine7 exhibited the most significant inhibitory effects among all of the screened compounds on the panel of the tested cell lines with IC50 values comparable to those of conventional anticancer agents such as cisplatin and etoposide. Abstract : Ethyl (4 S, 5 R, 6 R, 2 E )-5, 7-bis(benzyloxy)-4, 6-(isopropylidenedioxy)hept-2-enoate: C26 H32 O6 [ α ]D 24 = −22.7 ( c 0.22, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 S, 5 R, 6 R, 2 E ) Abstract : (4 S, 5 R, 6 R, 2 E )-5, 7-Bis(benzyloxy)-4, 6-(isopropylidenedioxy)hept-2-en-1-ol: C24 H30 O5 [ α ]D 25 = +4.2 ( c 1.28, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 S, 5 R, 6 R, 2 E ) Abstract : (4 R, 5 R, 6 S )-5-(Benzyloxy)-4-[(benzyloxy)methyl]-6-[(1′ S )-1′-isothiocyanatoallyl)]-2, 2-dimethyl-1, 3-dioxane: C25 H29 NO4 S [ α ]D 25 = +52.7 ( c 0.70, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 R, 6 S, 1′ S ) Abstract : (4 R, 5 R, 6 S )-5-(Benzyloxy)-4-[(benzyloxy)methyl]-6-[(1′ R )-1′-isothiocyanatoallyl)]-2, 2-dimethyl-1, 3-dioxane: C25 H29 NO4 S [ α ]D 25 = +2.9 ( c 0.24, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 R, 6 S, 1′ R ) Abstract : N -(1′ S )-1′-[(4″ S, 5″ R, 6″ R )-5″-(Benzyloxy)-6″-[(benzyloxy)methyl]-2″, 2″-dimethyl-1″, 3″-dioxan-4″-yl]allyl]-2, 2, 2-trichloroacetamide: C26 H30 Cl3 NO5 [ α ]D 24 = −47.1 ( c 0.14, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (1′ S, 4″ S, 5″ R, 6″ R ) Abstract : N -(1′ R )-1′-[(4″ S, 5″ R, 6″ R )-5″-(Benzyloxy)-6″-[(benzyloxy)methyl]-2″, 2″-dimethyl-1″, 3″-dioxan-4″-yl]allyl]-2, 2, 2-trichloroacetamide: C26 H30 Cl3 NO5 [ α ]D 24 = −28.3 ( c 0.12, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (1′ R, 4″ S, 5″ R, 6″ R ) Abstract : (4 S, 5 S )-5-[(1′ S, 2′ R )-1′, 3′-Bis(benzyloxy)-2′-hydroxypropyl]-4-vinyloxazolidine-2-thione: C22 H25 NO4 S [ α ]D 27 = −63.8 ( c 0.34, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 S, 5 S, 1′ S, 2′ R ) Abstract : (4 R, 5 S )-5-[(1′ S, 2′ R )-1′, 3′-Bis(benzyloxy)-2′-hydroxypropyl]-4-vinyloxazolidine-2-thione: C22 H25 NO4 S [ α ]D 23 = +67.8 ( c 0.37, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 S, 1′ S, 2′ R ) Abstract : (4 S, 5 S )-5-[(1′ S, 2′ R )-1′, 3′-Bis(benzyloxy)-2′-hydroxypropyl]-4-vinyloxazolidin-2-one: C22 H25 NO5 [ α ]D 27 = −26.5 ( c 0.26, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 S, 5 S, 1′ S, 2′ R ) Abstract : (4 R, 5 S )-5-[(1′ S, 2′ R )-1′, 3′-Bis(benzyloxy)-2′-hydroxypropyl]-4-vinyloxazolidin-2-one: C22 H25 NO5 [ α ]D 23 = +36.2 ( c 0.26, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 S, 1′ S, 2′ R ) Abstract : N -[(3′ S, 4′ S, 5′ R, 6′ R )-5′, 7′-Bis(benzyloxy)-4′, 6′-dihydroxyhept-1′-en-3′-yl]-2, 2, 2-trichloroacetamide: C23 H26 Cl3 NO5 [ α ]D 27 = −12.8 ( c 0.32, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (3′ S, 4′ S, 5′ R, 6′ R ) Abstract : N -[(3′ R, 4′ S, 5′ R, 6′ R )-5′, 7′-Bis(benzyloxy)-4′, 6′-dihydroxyhept-1′-en-3′-yl]-2, 2, 2-trichloroacetamide: C23 H26 Cl3 NO5 [ α ]D 28 = +34.7 ( c 0.60, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (3′ R, 4′ S, 5′ R, 6′ R ) Abstract : (4 S, 5 S )-4-Ethyl-5-[(1′ S, 2′ R )-1′, 2′, 3′-trihydroxypropyl]oxazolidin-2-one: C8 H15 NO5 [ α ]D 23 = +6.3 ( c 0.24, CH3 OH) Source of chirality:d -xylose Absolute configuration: (4 S, 5 S, 1′ S, 2′ R ) Abstract : (4 S, 5 R )-4-Ethyl-5-pentadecyloxazolidin-2-one: C20 H39 NO2 [ α ]D 24 = +5.1 ( c 0.76, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 S, 5 R ) Abstract : (3 S, 4 R )-3-Aminononadecan-4-ol: C19 H41 NO [ α ]D 24 = +14.0 ( c 0.35, MeOH) Source of chirality:d -xylose Absolute configuration: (3 S, 4 R ) Abstract : (4 R, 5 S )-3-Benzyl-5-[(1′ R, 2′ R )-1′, 2′, 3′-tris(benzyloxy)propyl]-4-vinyloxazolidin-2-one: C36 H37 NO5 [ α ]D 24 = +77.0 ( c 0.40, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 S, 1′ R, 2′ R ) Abstract : (4 R, 5 S )-3-Benzyl-4-ethyl-5-[(1′ S, 2′ R )-1′, 2′, 3′-trihydroxypropyl]oxazolidin-2-one: C15 H21 NO5 [ α ]D 23 = +74.2 ( c 0.26, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 S, 1′ S, 2′ R ) Abstract : (4 R, 5 R )-4-Ethyl-5-pentadecyloxazolidin-2-one: C20 H39 NO2 [ α ]D 24 = +40.0 ( c 0.16, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (4 R, 5 R ) Abstract : (3 R, 4 R )-3-Aminononadecan-4-ol: C19 H41 NO [ α ]D 23 = +12.7 ( c 0.22, CHCl3 ) Source of chirality:d -xylose Absolute configuration: (3 R, 4 R ),